Perencanaan Pembangunan Kalurahan Wirokerten: Sebuah Studi tentang Akses Gagasan dan Pengawasan Masyarakat - Abdul Aziz A. Ibrahim, Supardal (Program Studi Pembangunan Masyarakat Desa (D3), 2022)
Citizen participation in development planning is a necessity in accordance with Law Number 6 of 2014 concerning Villages, in fact not all villages apply the principle of participation in preparing development plans. Departing from this problem, the author intends to examine how the participatory village development planning process takes place and involves the Wirokerten community. Because community participation is still considered not too important in the agreement to express opinions and influence village development policy plans. The presence of the community is also still seen as a formalistic participation which is limited to approving policies designed by the village government. In addition, there are still many people who have not received information about village development planning. This study uses a qualitative research method using descriptive research that seeks to describe empirical facts of various phenomena that exist in the Wirokerten Village, through a process of observation and interviews with all stakeholders. The results show that the level of participation of Wirokerten residents in the planning process is not optimal. This shows that even though the residents are present in the forum, they have not conveyed much of their aspirations and ideas. Residents also have not yet gained access to and exercised oversight in village development planning.